Impact of SARS-CoV-2 pandemic on pulmonary hypertension out-patient clinics in Germany: a multi-centre study - Yogeswaran, Athiththan; Gall, Henning; Tello, Khodr; Grünig, Ekkehard; Xanthouli, Panagiota; Ewert, Ralf; Kamp, Jan C.; Olsson, Karen M.; Wißmüller, Max; Rosenkranz, Stephan; Klose, Hans; Harbaum, Lars; et al. (Pulmonary circulation, 2020)
Pulmonary hypertension is frequently underdiagnosed, and referral is delayed with subsequent impact on outcomes. During the SARS-CoV-2 pandemic, restrictions on daily life and changes in hospitals' daily routine care were introduced in Germany. This multi-centre study provides evidence for a negative influence of these restrictions on patient care in pulmonary hypertension expert referral centres.